Biochemical screening for trypsin inhibitor factors and morphomolecular characterization of soybean (Glycine max L. Merr.) - Verma, Khushbu; Talukdar, Akshay; Shivakumar, M.; Kumar, Bhupender; Lal, S.K.; Srivastava, Nidhi; Sapra, R.L.; Harish, G.D.; Girmilla, Vanishree (The Indian Journal of Genetics and Plant Breeding, 2016)
A set of 101 diverse soybean genotypes were biochemically analyzed for trypsin inhibitor (TI) contents, and were characterized with morphological and molecular markers. The TI content in the seeds ranged from 14.65 to 175.52 mg g–1 soymeal. The Indian soybean varieties were found to contain higher amount of TI (58.79-126.78 mg g–1 soymeal) while PI542044, an exotic germplasm was found to contain the least (14.65 mg g–1 soymeal).Morphological characterization with 16 qualitative and quantitative traits revealed significant variations and grouped the genotypes in to three major groups with overall mean dissimilarity value of 0.30. Genetic diversity study conducted with 100 simple sequence repeat (SSR) markers detected higher level of polymorphism (71%). Of the total 221 alleles amplified, 65 were rare (frequency